(untitled) - Ryan, Pam Munoz; Selznick, Brian (Scholastic Press, 2002)
An introduction to the life of Marian Anderson, extraordinary singer and civil rights activist, who was the first African American to perform at the Metropolitan Opera, whose life and career encouraged social change.
"Season of two thousand and two"--T.p.
Statement of responsiblity reads, libretto by Pam MuSnoz Ryan ; staging by Brian Selznick.
Includes discography.
Keywords: Anderson, Marian; Juvenile literature; Anderson, Marian; Biography; Women; Biography; African Americans; Singers; Contraltos; African American singers; United States; Biography; Biography